Immunohistochemical Expression of Ki-67 and p53 in Different Grades of Phyllodes Tumors of the Breast and its Association with Clinicopathological Characteristics - Tahir, Sana; Avesi, Lubna; Danish, Farheen; Hassan Shamim, Saba; Bukhari, Uzma; Muhammad Ali, Farah (Journal of Postgraduate Medical Institute, 2024)
Objective:This study aimed to investigate the immunoreactivity of Ki67 and p53 in Phyllodes tumors (PTs) of the breast and assess their correlation with clinicopathological features, including PT grade and clinical parameters. Methodology: A comparative, analytical cross-sectional design was employed to evaluate Ki67 and p53 immunoreactivity in the Phyllodes tumors. The research was conducted at the Histopathology Department, DDRRL/DUHS, Karachi, over an 8-month period. Ethical approval was also obtained from DUHS's board. Purposive nonprobability sampling was used to select the patients. Immunohistochemistry, performed on FFPE tissue blocks, involved evaluating Ki67 and p53 staining. Statistical analysis (descriptive, chi-squared, and Kruskal Wallis tests) was carried out using IBM SPSS version 26, and a p-value <0.05 was considered statistically significant. Results:The research involved 50 patients, comprising benign 19 (38%), borderline 23 (46%), and malignant 08 (16%) PTs. Malignant tumors exhibited significantly higher expression of Ki67 and p53 compared to benign and borderline tumors (p < 0.005). Clinicopathological parameters, such as tumor mobility, skin ulceration, tumor borders, leaf-like architecture, stromal overgrowth, necrosis, and surgical margins, showed significant associations with Ki67 and p53 expression (p < 0.005). These results recommend that Ki67 and p53 may serve as valuable diagnostic and prognostic markers in PTs. Conclusion: The study's results indicate that the immunohistochemical evaluation of Ki67 and p53 could be beneficial in the diagnosis of PTs. The association between Ki67 and p53 expression and various clinicopathological features, particularly PT grade, highlights their potential clinical significance. Further research could contribute to the advancement of standardized diagnostic and prognostic criteria for PTs, improving patient management and outcomes.